Renal microangiopathy induced by lenvatinib in hepatocellular carcinoma: a case report and literature review - Xue, Cheng; Cui, Linlin; Chen, Jiaxin; Liu, Yang; Deng, Yufei; Xu, Wenyi; Mao, Zhiguo; Wu, Jun (Frontiers in Pharmacology, 2024)
Lenvatinib, a multi-target inhibitor of receptor tyrosine kinases, has been increasingly used in the treatment of advanced hepatocellular carcinoma (HCC). However, its association with renal adverse effects, including proteinuria and renal microvascular complications, was not fully understood in HCC patients. We reported a case of a 68-year-old male with a history of hypertension, diabetes mellitus, and hepatitis C virus (HCV) infection, diagnosed with primary HCC in 2015. Despite previous treatments, he was started on lenvatinib due to tumor recurrence. Initially, he had mild proteinuria, which significantly worsened post-lenvatinib initiation, accompanied by fluctuating renal function and severe edema. The diagnosis of lenvatinib-induced renal microvascular damage was confirmed through renal biopsy, which showed glomerular sclerosis, tubulointerstitial changes, and arteriolosclerosis. Discontinuation of lenvatinib led to significant improvements in proteinuria and edema. Subsequent cancer recurrence was managed with microwave ablation and immunotherapy, with satisfactory recovery. The potential for lenvatinib to induce significant renal microvascular disease, as demonstrated in this case, emphasizes the importance of vigilant renal monitoring and personalized therapeutic strategies in patients treated with lenvatinib for HCC. Early intervention and dose adjustment may be crucial in preventing severe renal impairment, highlighting the significance of tailored treatment plans in the management of advanced HCC patients especially with pre-existing risk factors.